Effect of esketamine intravenous anesthesia combined with nerve block in pediatric upper limb short orthopedic surgery - YANG Jingyi，WULAN Nari (Zhongguo linchuang yanjiu)
Objective To evaluate the effect of esketamine intravenous anesthesia combined with brachial plexus nerve block on pain management in pediatric upper limb short orthopedic surgery. Methods A prospective study was conducted on 132 children scheduled for upper limb short orthopedic surgery at the Second Affiliated Hospital of Inner Mongolia Medical University from December 2022 to December 2023. The children were divided into two groups using random number table methods：the esketamine group and the control group, with 66 children in each group. Both groups received intravenous anesthesia combined with ultrasound - guided brachial plexus nerve block. Before performing the nerve block, the esketamine group was administered esketamine 0.3 mg/kg intravenously, while the control group received propofol 3 mL/kg( 10 ml：0.1 g) intravenously. Pain levels were assessed using the face, legs, activity, crying, consolability( FLACC) scale at different time points before and after surgery. After surgery, the first time of ibuprofen taken by children, the total dose of ibuprofen within 24 hours, and the occurrence of adverse reactions were recorded. Results All surgeries were completed successfully without severe postoperative complications. There were no statistically significant difference in the FLACC scores between the two groups before surgery, 2 h post - surgery, and 24 h post-surgery( P>0.05) . However, at 4, 6, 8, and 16 h post-surgery, the esketamine group had significantly lower pain scores compared to the control group( P<0.05) . In the esketamine group, the first time of ibuprofen taken by children was later［( 8.71±4.63) h vs( 5.12±2.01) h, t=5.778, P<0.01］, and the total ibuprofen dose within 24 h post-surgery was lower［( 6.42±1.50) h vs( 9.22±4.33) h, t=4.964, P<0.01］, as well as the incidences of adverse reactions during surgery and postoperative delirium were significantly lower compared to the control group( P<0.05) . Conclusion Esketamine intravenous anesthesia combined with nerve block can provide an effective analgesia in pediatric upper limb short orthopedic surgery, reduce the use of postoperative analgesic drugs, and has fewer adverse reactions.